#KerjaSamaAI: Mediasi Serial Manfaat, Kekhawatiran, dan Peluang dalam Efek Penggunaan AI terhadap Literasi AI - Febriawan, Iqbal Maesa; Yusup, Mahmud (Universitas Airlangga, 2025)
Stemmed from the debate on whether AI understanding should be theory-driven before practice or whether concrete experience is more effective, this study examines the relationship between AI literacy and AI usage variation at the workplace, with perceived AI benefits, AI concerns, and AI opportunities as the mediating variables. Data were collected from 447 employees through an online survey and analyzed using structural equation modeling (SEM). The results indicate that AI usage variation plays a greater role in enhancing AI literacy than the other way around. Additionally, the perceived benefits of AI significantly increase perceived opportunities, which ultimately increases AI literacy, whereas concerns about AI have no significant effect. These findings confirm that hands-on experience is more effective in developing AI understanding than a theory-based approach. Furthermore, the study highlights the importance of communicating AI benefits to encourage adoption and improve AI literacy in professional environments.